Textiles in Indonesia : problems of import substitution - Palmer, Ingrid (New York : Praeger, 1972)
This text is a case of economic investigation into the Indonesian textile industry.
Includes bibliographical references: p. 381-399.
ne 21/01/2019
Loans
Keywords: Cotton trade; Textile industry; Cotton manufacture; Indonesia